AN EMPIRICAL MODEL FOR FORECASTING ELECTRIC GENERATION FOR NEARSHORE ENERGY POTENTIAL IN THAILAND - Phaiboon, Supachai; Phokharatkul, Pisit (Journal of Applied Engineering Science, 2022)
This paper presents electrical energy forecasting from near shore wave potential in the Gulf of Thailand using an empirical model. An electric generator was installed on the near shore to perform measurements and create an empirical model for predicting electric generation. In order to forecast the capacity of the electric generation from sea waves with sufficient electricity consumption, the household data in the Gulf of Thailand and the Andaman Sea were collected from the year 2012 – 2019 to forecast the increasing rate of the number of households in the five years period (2021-2025). Cost and payback period were analyzed in each location in order to invest the renewable energy generation.